Art meets Science and Spirituality in a changing Economy. - Tisdall, Caroline; Wijers, Louwrien; Kamphof, Ike ('s-Gravenhage : SDU Uitgeverij, 1990)
This book also serves as the catalogue for 'Science and Spirituality in a changing Economy', an initiative comprised of the following events: - The opening ceremony (8 September 1990) at the University of Amsterdam presided over by H.H. the 14th Dalai Lama of Tibet, who was awarded the 1989 Nobel Prize for Peace. - The five-day panel program (10 through 14 September 1990) at the Stedelijk Museum Amsterdam of artists meeting with scientists, representatives of spiritual traditions and economists. - The exhibition at the Museum Fodor in Amsterdam (8 September through 14 October 1990). Eight artists from Amsterdam invited eight foreign artists to collaborate on works addressing the theme 'Art meets Science and Spirituality in a changing Economy'.
boek
Keywords: Rauschenberg, Robert; Cage, John; van der Heyden, J.J.; Weiner, Lawrence; Abramovic, Marina; General Idea; van Summeren, Ton; Chamberlain, John; Scholte, Rob; Schuyff, Peter; Fortuyn/O'Brien; Spalletti, Ettore; Puckey, Thom; Orr, Eric; Heynen, Pieter; Heynen, Abby; Rollins, Tim + K.O.S.; Bastiaans, Christiaan; Ida, Shoichi; Mantje, Aldert; Bauntuch, Troy